The Effects of Group Psychotherapy on the Adjustment of Four 12-Year-Old Boys with Learning and Behavior Problems. - DuPlessis, Jean M.; Lochner, L.M. (Journal of Learning Disabilities, 1981)
Describes a program and approach for group therapy for use with small groups of adolescent boys with general adjustment, socialization and peer-group communication problems. Enhancement of the progress made in the social, emotional and scholastic fields by the program; Improvement in boys' patterns of communication, attitudes and general adjustment as shown by feedback from parents, teachers and personal observation.